Design of half-metallic Heusler-based superlattices with vanishing net magnetization - Tirpanci, Aban; Sasioglu, E.; Galanakis, I. (Amer Inst Physics, 2013)
Employing first-principles electronic structure calculations, we show that it is possible to achieve half-metallic antiferromagnetism in artificial superlattices based on Heusler compounds. Suitable alternation of full-Heusler compounds with more and less than 24 valence electrons in the unit cell results in superlattices with zero total spin magnetic moment keeping the half-metallic character of the initial compounds. We demonstrate it considering superlattices made up from Mn2TiGe (Mn2VGa) and Co2TiGe (Co2VGa) compounds, which have 22 and 26 valence electrons, respectively. Moreover, these compounds posses similar lattice constants and have been already grown as thin films making them promising for spintronics devices. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4789361]
Keywords: Ab-Initio; Alloys; Antiferromagnets; 1st-Principles; Transport; State